2015
DOI: 10.1016/j.bmc.2014.12.067
|View full text |Cite|
|
Sign up to set email alerts
|

Naturally occurring polyphenol, morin hydrate, inhibits enzymatic activity of N-methylpurine DNA glycosylase, a DNA repair enzyme with various roles in human disease

Abstract: Interest in the mechanisms of DNA repair pathways, including the base excision repair (BER) pathway specifically, has heightened since these pathways have been shown to modulate important aspects of human disease. Modulation of the expression or activity of a particular BER enzyme, N-methylpurine DNA glycosylase (MPG), has been demonstrated to play a role in carcinogenesis and resistance to chemotherapy as well as neurodegenerative diseases, which has intensified the focus on studying MPG-related mechanisms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 38 publications
0
7
0
1
Order By: Relevance
“…DNA binding studies were performed in a Biacore T100 system (BIAcore, Uppsala, Sweden) as published previously [94, 95]. Briefly, the affinity of DY131, GSK4716, and mitoxantrone for DNA was tested using a 50-mer oligonucleotide:…”
Section: Methodsmentioning
confidence: 99%
“…DNA binding studies were performed in a Biacore T100 system (BIAcore, Uppsala, Sweden) as published previously [94, 95]. Briefly, the affinity of DY131, GSK4716, and mitoxantrone for DNA was tested using a 50-mer oligonucleotide:…”
Section: Methodsmentioning
confidence: 99%
“…Base excision repair (BER) is one of the most commonly used DNA repair mechanisms in cells. Poly(ADP‐ribose)polymerase 1 (PARP1), N ‐methylpurine‐DNA glycosylase (MPG), and X‐ray repair cross‐complementary 1 (XRCC1) play indispensable roles in DNA damage BER (Dixon et al, 2015; Hinz & Czaja, 2015; Valérie et al, 2002). It has been found that in mouse embryonic fibroblasts, H3K9me3 interacts with acetyltransferase Tip60 at the site of DNA double‐strand breaks, triggering downstream DNA damage responses to repair the breaks (Sun et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Based on this observation, a series of structural analogs has been computationally designed to inhibit TagA from Leptospira interrogans, the infectious agent of leptospirosis, although no experimental evidence was provided for their activity against the enzyme or the pathogen [231]. A natural flavonol, morin, inhibits MPG [78] (Table 2).…”
Section: Alkylation Damage Repair: Dual Consequencesmentioning
confidence: 99%